Use of short tandem repeat sequences to study Mycobacterium leprae in leprosy patients in Malawi and India. - Saroj K Young; Jorg M Ponnighaus; Suman Jain; Sebastian Lucas; Sujai Suneetha; Diana N J Lockwood; Douglas B Young; Paul E M Fine (PLoS Neglected Tropical Diseases)
Background Inadequate understanding of the transmission of Mycobacterium leprae makes it difficult to predict the impact of leprosy control interventions. Genotypic tests that allow tracking of individual bacterial strains would strengthen epidemiological studies and contribute to our understanding of the disease. Methodology/principal findings Genotyping assays based on variation in the copy number of short tandem repeat sequences were applied to biopsies collected in population-based epidemiological studies of leprosy in northern Malawi, and from members of multi-case households in Hyderabad, India. In the Malawi series, considerable genotypic variability was observed between patients, and also within patients, when isolates were collected at different times or from different tissues. Less within-patient variability was observed when isolates were collected from similar tissues at the same time. Less genotypic variability was noted amongst the closely related Indian patients than in the Malawi series. Conclusions/significance Lineages of M. leprae undergo changes in their pattern of short tandem repeat sequences over time. Genetic divergence is particularly likely between bacilli inhabiting different (e.g., skin and nerve) tissues. Such variability makes short tandem repeat sequences unsuitable as a general tool for population-based strain typing of M. leprae, or for distinguishing relapse from reinfection. Careful use of these markers may provide insights into the development of disease within individuals and for tracking of short transmission chains.